E-commerce and entrepreneurship for African Continental Free Trade Area (AfCFTA): A readiness conceptual framework - Frank Makoza (African Continental Free Trade Area (AfCFTA), 2023)
African governments have ratified the African continental free trade area (AfCFTA) to support elimination of tariffs and taxes on intra-African trade on goods, services and investment; and promote integration that can lead to socio-economic growth. This paper proposes a readiness conceptual framework of electronic commerce and entrepreneurship. The study highlighted factors that African countries may consider to fully reap the benefits of the African continental free trade area. The factors include technology, legal frameworks, infrastructure, social norms, culture, economy, politics and entrepreneurship. The proposed readiness conceptual framework can be validated in further studies. The study contributes towards literature on e-commerce and entrepreneurship in the context of AfCFTA.
Keywords: 330; African continental free trade area; e-commerce; e-readiness; entrepreneurship